Working Conditions and Job Satisfaction of China's New Generation of Migrant Workers: Evidence from an Inland City - Huashu Wang; Lei Pan; Nico Heerink (Institute for the Study of Labor (IZA), 2013)
China is experiencing notable changes in rural-urban migration. Young, more educated migrants with different attitudes towards living and working form an increasing share of the migrant labour force. At the same time, the destinations of migrants are changing as a result of government policies and the global financial crisis. More migrants than before find jobs in medium and small size cities, often located in western and central China. Understanding the characteristics and attitudes of the changing migrant labour force is becoming a major challenge in sustainably managing migration flows and urbanization. Little hard evidence is available on the working conditions and job attitudes of migrant workers, particularly for inland China. The purpose of this paper is to provide insights into the characteristics, working conditions and job attitudes of the new generation of migrants, defined as those born in the 1980s and 1990s, as compared to the traditional generation in a typical medium-size city in western China. Data collected through a household survey conducted among 1,048 migrants in Guiyang City, capital of Guizhou Province, are used for this purpose. We find significant differences in occupational characteristics and working conditions between the two generations. Contrary to popular beliefs, we find that the level of job satisfaction is higher among the new generation of migrants. Using an ordered logit model to examine factors contributing to job satisfaction, we find that age and gender do not have a significant impact for young migrants, while working conditions play a major role. Among these, it is not so much the income level that matters for young migrants, but other working conditions. Using a Blinder-Oaxaca decomposition, we derive that it is mainly the difference in working conditions and other endowments that explains the higher job satisfaction of young migrants, not the differences between generations in the valuations of these endowments.
Keywords: J61; O15; 330; migrant workers; new generation; working conditions; job satisfaction; China